Adsorption of Hg(II) from Aqueous Solution of Activated Carbon Impregnated in Copper Chloride Solution - Hai1, N.T.T.; Hue1, N.T.; Trung2, D.Q. (Asian Journal of Chemistry, 2013)
Study on removal of mercury in aqueous solution by available and low-cost materials with high treatment efficiency is now-a-day a hot topic. In the present work, activated carbon derived from coconut shell was impregnated with copper chloride solution and removal of Hg(II) from aqueous solution by these carbons was effectively demonstrated. Adsorption of Hg(II) from aqueous solutions was carried out under different experimental conditions by varying solution pH, agitation time, Hg(II) concentration and carbon dosage. It was shown that Hg(II) uptake decreases with increasing pH of the solution and optimum pH value is 6 and equilibrium time was attained at 60, 90 min for activated carbon, copper chloride solution-impregnated activated carbon, respectively. The monolayer adsorption capacity of these particular adsorbents were obtained as 90.9 and 167 mg/g for activated carbon and copper chloride-impregnated activated carbon, respectively. It was determined that Hg(II) adsorption follows both Langmuir and Freundlich isotherms as well as pseudo-first-order kinetics.